Cyberbullying: Definition, Prevalence, Effects, Risk and Protective Factors - Burak Akdeniz; Aysun Doğan (Psikiyatride Güncel Yaklaşımlar, 2024)
Cyberbullying is defined as intentional, repetitive, and harmful behaviors carried out using computers, cell phones, or other electronic devices. In recent years, there has been an increase in the rates of cyberbullying parallel to the rise in Internet usage. Particularly among adolescents, the prevalence of cyberbullying and cyber victimization are quite high. Adolescents who cyberbully or cyber victim face serious mental health problems. In this reason, efforts should be made to prevent adolescents from being exposed to these negative effects. It is crucial to identify the risk factors and protective factors related to cyberbullying, as they can guide preventive interventions. The review aims to provide a comprehensive perspective on the risk factors and protective factors influencing cyberbullying. Furthermore, information was provided regarding the definition, historical trend, prevalence, and consequences of cyberbullying. In this review, firstly, the definition of cyberbullying is provided, followed by a detailed discussion of its history, prevalence, risk factors, and protective factors. It is expected that the study, which comprehensively explains the factors related to cyberbullying, will contribute to the literature on cyberbullying and provide guidance to professionals working in this field."